Research in Clinical Practice - Smith, Daron. (Springer London : Imprint: Springer, 2013)
Research in Clinical Practice is a neat, pocket-sized reference guide examining how to get the most from actively participating in research. Including how to begin, avoiding pitfalls, whom to approach and what questions to ask - all significant practicalities for conducting research in the reader's area of interest. Each reader will learn how to make the best use of such a valuable time. Written by two experienced surgeons, both of whom achieved post graduate research degrees, Research in Clinical Practice, is an essential tool for clinicians embarking on a research project as well as those who are new to supervising researchers.